Peran Taman Pendidikan Al-Qur’an Dalam Meningkatkan Pembelajaran Pendidikan Agama Islam (Studi Pada Taman Pendidikan Al-Qur’an Nur Sabilal Muhtadin di Dusun Cahaya Desa Pelimpaan Kecamatan Jawai) - Shopia; Hifza; Astaman (Fakutas Tarbiyah Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2023)
The aim of this research is to reveal the role of TPQ in improving Islamic religious education learning at TPQ Nur Sabilal Muhtadin in Cahaya Hamlet, Pelimpaan Village, Jawai District. The research has three objectives, namely: First, to find out the Islamic religious education material taught in TPQ Nur Sabilal Muhtadin. Second, find out about Islamic religious education learning activities in TPQ Nur Sabilal Muhtadin. Third, knowing the role of teachers in Islamic religious education learning activities. This research is a qualitative descriptive study which aims to find out how TPQ teachers improve PAI learning. The subjects of this research were TPQ teachers and students Nur Sabilal Muhtadin. Data collection tool techniques namely; observation, interview, documentation. Meanwhile, the data analysis techniques used are data reduction, data presentation, verification and drawing conclusions. Then the data validity techniques used are triangulation and member checks. The results of this study are; The Islamic religious education material taught is material about faith, morals, worship, fiqh, the Koran, and Islamic history. Islamic religious education learning activities consist of opening, core and closing activities. The role of the teacher in learning Islamic religious education is as an informator, organizer, motivator, director, initiator, facilitator, transmitter, mediator and evaluator.